Modelling approach to assess control scenarios for key livestock diseases - CGIAR Research Program on Livestock (2019)
The approach was developed and tested for an important pig diseases in Vietnam, but can be applied to any other livestock production systems and diseases elsewhere. Currently the modelling approach is being used for pig diseases in Uganda.